Professional Burnout, Sources of Stress and Life Satisfaction at Educational Staff in the Secondary Education in the Republic of Macedonia (Annual of the Faculty of Philosophy in Skopje, 2018)
The aim of this research was to answer the question about whether there is a differenceregarding the professional burnout, the sources of stress and life’s pleasure amongthe teachers working in the secondary schools in RM associated with the place of work, thesex and the length of service. The specimen includes 440 educational workers, out of which220 are from the secondary schools in the interior of the RM and 220 are from the secondaryschools in Skopje. The research was carried out in the period between February and April2018.The results show that there is not a statistically significant difference in the levelof manifestation of the professional burnout, the sources of stress and life’s pleasure betweenthe teachers working in the interior secondary schools in RM and the ones working inSkopje. The research has shown that the age and length of service considerably correlatewith the professional burnout and the level of experienced stress, whereby the older groupwith the longest length of service is the most susceptible to the influence of the professionalburnout and the sources of stress in the teachers.
Keywords: PROFESSIONAL BURNOUT; SOURCES OF STRESS AND LIFE’S PLEASURE